Student’s Interest on Vocabulary Through Falou Application - Muhammad, Aditya; Sukma Dara Damanik, Emeliya (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This qualitative research investigates students' interest in vocabulary, which is considered an important tool in language learning. Students can improve their knowledge and learning through the use of technology. The use of technology in education is expected to support educators and learners during classroom activities. Therefore, this study focuses on the use of the Falou application to learn vocabulary. Data were collected through observations and interviews with students before using the Falou app and after using the Falou app for vocabulary improvement. The results showed that students' interest in learning vocabulary increased after using the Falou application as an English language learning medium. It can be said that the use of the Falou application in the vocabulary learning process is an effective solution for students at Mts Madani Ikhwanul Hasanah.